Dirty gourmet plant power : food for your outdoor adventures - Trudeau, Aimee; Nielson, Emily; Kwan, Mai-Yan (Skipstone, 2023)
"From the bestselling authors of Dirty Gourmet: Food for Your Outdoor Adventures, comes a brand new cookbook! The recipes in Dirty Gourmet Plant Power focus on vegan recipes with a global twist. In the spirit of inclusivity and accessibility, the authors have included snacks and meals that work great for play dates at the local park or picnics on the beach, as well as food-fuel for urban and day hikes and on longer wilderness outings. With details on how to do your own dehydrating--though with no shaming for buying pre-dehydrated goods--and helpful tips about equipment and basics to keep on hand, Dirty Gourmet Plant Power will have you enjoying scrumptious recipes wherever you head outside!"--